Specifics of a Higher Institute of Economics and Possibilities to Decentralize Its System of Management - Angelov, Angel (Research Papers, 2007)
The paper analyses the specifics of an institution of higher learning in the sphere of economics as a major non-production organization and focuses on the education product, educational process and the end product of the fundamental structural unit of a tertiary learning institution, as well as its basic structural unit, the faculty.A comprehensive study of the educational and the end product has been made. The author argues the need to design and set up a new type of faculties, i.e. ones greater in size and in scope, to be transformed into main structural units as a run-up to the management system decentralization.The paper also outlines the relationship and the interdependence between the size of the faculty and its independence, including in terms of its finances, as well as the possibilities for the decentralization of the management system based on faculties of the new types.